Wave Propagation Scattering Due to Defect on Thin Composite Plates - Z. M., Hafizi; Epaarachchi, J.; Lau, K. T. (2013)
The engineering structures which based on laminated composites, have a high probability of unexpected damage development during services. The damage formations must be monitored from the beginning before it headed towards structural failure which could result in substantial damage. This lead to the necessity of Structural Health Monitoring (SHM) system to be installed during the construction of laminated composite structures. However, an understanding of damage area detection and damage characteristics is essential, before a SHM system can be integrated into the structures. This article presents the effects of propagating wave propagation through an existing damage on composite plates. Theoretically, a propagating wave that started from any source will vary when crossing an area with damage. This study shows a high frequency wave propagation (kHz range) show different reactions when passing through the damaged area, compared with the low frequency wave propagation. Results of the study will lead to good damage detection method, which utilizing the available vibration source; especially for the condition monitoring of thin laminated composite structures.